Optimization of Red Ginger (Zingiber officinale var. Rubrum) Extraction Using Microwave Assisted Hydrodistillation Method - Nurjanah, Sarifah; Rosalinda, Sari; Andina, Dwita Putri (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Red ginger is a spice plant that has high economic and social value. One of the uses of red ginger is to process it into a product, namely essential oil. This study aims to determine the optimization of the extraction process conditions on solvent volume, time, and extraction power that can produce optimum yield and residual content of red ginger essential oil solvent. The extraction was carried out with the help of microwaves. The research method is experimental design and optimization process with Response Surface Methodology (RSM) type Box-Behnken Design (BBD). The results showed that the optimum yield was at 700 mL solvent volume, 1 min extraction time, and 10% power (69.9 watts) with the equation Y = 0.2076 + 0.0262A – 0.0300B – 0.0013C and the concentration conditions the optimum remaining solvent with the equation Y = 4.98 – 1.0000A + 4.56B + 5.44C. The optimal yield of red ginger essential oil was 0.205%, with a residual solvent content of 3.8%, specific gravity 0.885, acid number 1.399, refractive index 1.485. The results of the optimum residual solvent content of -6.023%. Based on the results obtained, the yield value with the help of microwaves is higher than that without the help of microwaves. Keywords: Essential oil, Microwave, Residual solvent content, Response surface methodology (RSM), Yield.